A brief campaign to prevent diabetic ketoacidosis in children newly diagnosed with type 1 diabetes mellitus: The NO‐DKA Study. Issue 7 (1st August 2018) - Derraik, José G. B.; Cutfield, Wayne S.; Maessen, Sarah E.; Hofman, Paul L.; Kenealy, Timothy; Gunn, Alistair J.; Jefferies, Craig A.
Abstract : Objective: New‐onset diabetic ketoacidosis (NO‐DKA) is entirely preventable with early recognition of the symptoms of type 1 diabetes mellitus (T1D). In this study, we aimed to assess whether a simple and easily delivered educational campaign could reduce the risk of DKA. Methods: A poster highlighting key features of new‐onset T1D was delivered once a year over 2 years to mailboxes of over 460 000 individual residential households in the Auckland region (New Zealand). In the first year, the campaign poster was also delivered to all general practices in the region. Families of all newly diagnosed cases of T1D in children answered a brief questionnaire to ascertain whether the campaign reached them. Results: Over the 24‐month period covered by this study, 132 new cases of T1D were diagnosed in children and adolescents in Auckland. There were 38 cases (28.8%) of DKA, which is similar to the average over the previous 5‐year period (27.0%). The caregivers of three children reported both seeing the campaign poster and seeking medical attention as a result. None of these three children were in DKA at diagnosis; they were aged 6.3 to 9.7 years, and of New Zealand European ethnicity. Conclusions: A non‐targeted campaign to raise awareness of diabetes symptoms in youth led only a few caregivers to seek timely medical attention. Overall, this once‐yearly untargeted campaign to raise awareness of diabetes symptoms in youth had limited impact. More effective strategies are required, possibly involving sustained targeted education of medical practitioners.